Relationship among body condition at parturition, decrease of backfat thickness and weight during the lactation and the interval from weaning to oestrus of sows - Guedes, Roberto Maurício Carvalho; Nogueira, Raimundo Hilton Girão (Brazilian Journal of Veterinary Research and Animal Science, 2000)
The main objectives of this study were to verify the relationship among body condition at parturition, decrease of backfat thickness and weight during the lactation and the interval from weaning to oestrus of sows. It was performed with 10 gilts and 10 fifth, sixth and seventh parity Camborough sows. The average breeding age and weight of the gilts were respectively 231 days and 149.5 kg. During lactation all females were fed a wet diet (3.34 Mcal/kg, 17% CP), ad libitum. The average daily food consumption was 5.233 for gilts and 5.721 kg for multiparous sows. Ultrasonic measurements of backfat at the P2 site were recorded on day 6 before and days 2, 7, 14, 21 and 25 after parturition. Body weight was recorded on the same dates, except the day before parturition. Sows were divided into 2 groups according to their backfat thickness 6 days before parturition. Sows with a backfat thickness of 16 mm or less were assigned to the L-group, while those with a backfat thickness more than 16 mm were assigned to the H-group. After weaning, the interval from weaning to oestrus was recorded. The percentage of total weight loss during lactation was slightly higher (not significant) in the H-group (-4.26%) than in the L-group (-2.64%). The percentage of backfat thickness decreased in both groups from 6 days before parturition until day 25 of lactation, but the decrease was highest in the H-group (p < 0.03). The weaning-oestrus interval did not differ significantly between the 2 groups. In conclusion: there was no correlation between percentage of weight loss (total) and weaning to oestrus interval, or percentage of backfat thickness loss (total or by periods) and weaning-oestrus interval, or percentage of weight loss (total or by periods) and percentage of backfat thickness loss (total or by periods). On the other hand, there was a significant positive correlation between weaning-oestrus interval and percentage of weight loss during the third week of lactation.